Effects of sleep disorders on decision-making during competition in female soccer players - Fossati Invernizzi, Camila; Florencia Ferrero, Paula (International Journal of Neurology, 2024)
Currently, sleep is a factor that is not considered when deciding in game situations in matches and affects the sports performance of the players. The research seeks to explore the effects of sleep disorders on decision making during competition, this being a quasi-experimental and quantitative study with a non-experimental design, having an explanatory scope, and the data will be taken longitudinally. To obtain the data, the Pittsburgh Questionnaire [PSQI] (1988), Smartwatches, a survey in digital form to analyse the quality of sleep of the players and study the sociodemographic variables and sleep hygiene education session are used. The type of sampling was non-probabilistic, with a purposive technique, since the sports women were previously known. Based on the results obtained, the female soccer players of the UAI Urquiza club, after participating in the informative session, had increases in their sleep quality (± 30%), thus increasing their effective decision making (± 20%) for the match and for their performance. Concluding that sleep hygiene education sessions should be implemented for high performance athletes in all sports clubs, as well as for coaches and family members.